Exercise-induced second-degree atrioventricular block in endurance athletes - Doutreleau, S.; Pistea, C.; Lonsdorfer, E.; Charloux, A. (Medicine & Science in Sports & Exercise, 2013)
Training induces volume- and time-dependent morphological and functional changes in the heart. Heart rhythm disorders, such as atrial arrhythmia (including atrial fibrillation and atrial flutter), are a well-established consequence of such long-term endurance practice. Although resting bradycardia and first-degree atrioventricular persist in veteran athletes, a higher conduction system impairment has never been reported neither at rest nor during exercise. We report here two cases of Type II second-degree atrioventricular block occurring during exercise in middle-age well-trained athletes. Because animal and human studies suggest that a progressive myocardial fibrosis could explain such phenomenon, long-term training could also have consequences on the conduction pathways.